2015
DOI: 10.1093/jrr/rrv059
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 100-μT extremely low frequency electromagnetic fields exposure on hematograms and blood chemistry in rats

Abstract: The aim of this study was to test whether extremely low frequency electromagnetic fields (ELF EMFs) affect health or not. Here, we constructed a 100-μT/50 Hz electromagnetic field atmosphere. A total of 128 rats were randomly assigned into two groups: the ELF EMF group and the sham group. The ELF EMF group was exposed to 100-μT/50-Hz ELF EMF for 20 h per day for three months; at the same time the other group was exposed to a sham device without ELF EMF. During the three months, the weight was recorded every 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 38 publications
1
15
0
2
Order By: Relevance
“…Previous studies have indicated that welders exposed to PF-EMFs, at intensities between 100 and 250 µT, had no significant change in the hematopoietic system, including total and differential white blood cells (WBCs), red blood cells (RBCs), hemoglobin, and platelets [Dasdag et al, 2002]. Similarly, we have revealed that exposure to a 50-Hz PF-EMF at 100 μT exerted no effect on those indicators in rats [Lai et al, 2016b]. However, several pooled analyses have shown that children with a residential EMF exposure level above 0.4 μT might have an increased risk of leukemia [Ahlbom et al, 2000;Kheifets et al, 2010].…”
Section: Introductionmentioning
confidence: 52%
See 3 more Smart Citations
“…Previous studies have indicated that welders exposed to PF-EMFs, at intensities between 100 and 250 µT, had no significant change in the hematopoietic system, including total and differential white blood cells (WBCs), red blood cells (RBCs), hemoglobin, and platelets [Dasdag et al, 2002]. Similarly, we have revealed that exposure to a 50-Hz PF-EMF at 100 μT exerted no effect on those indicators in rats [Lai et al, 2016b]. However, several pooled analyses have shown that children with a residential EMF exposure level above 0.4 μT might have an increased risk of leukemia [Ahlbom et al, 2000;Kheifets et al, 2010].…”
Section: Introductionmentioning
confidence: 52%
“…In contrast, another study found no statistically significant alteration in hematochemistry when rats were exposed to a 50-Hz PF-EMF at 5 µT for 12 weeks or 44 weeks [Margonato et al, 1995]. Moreover, results from other studies have indicated that either 10 or 100 µT 50-Hz PF-EMF exposure could affect blood chemistry parameters (e.g., TC, HDL, electrolytes, and glycemia) in humans [Selmaoui et al, 1999] and rats [Lai et al, 2016b]. These various observations might be due to the different exposure intensities and durations.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…Therefore, different experiments with various examinations should be designed to test and verify the effects of EMF exposure on the cardiovascular system. Previously, we found that 100 µT EMF, which is the threshold of public exposure, did not affect the cardiovascular system and other organs (4,(23)(24)(25)(26). In the current study, we elevated the intensity to 500 µT, which is the threshold of occupational exposure, to explore whether it would exert damages in the cardiovascular system in rats.…”
Section: Introductionmentioning
confidence: 74%